Stable water isotopes and the physical environment - Roland Souchez; Réginald Lorrain; Jean-Louis Tison (Belgeo)
This paper presents the characteristics of the fractionation of water isotopes which occurs during evaporation and freezing of water. It shows how these characteristics can be used for studying some aspects of the physical environment, namely hydrological and glaciological issues. On the one hand, case studies regarding the hydrological cycle are considered. They deal with the relative contributions of runoff and groundwater to the discharge of rivers, of plant transpiration and direct evaporation in the arid regions atmosphere and of different water sources in aquifer recharge. On the other hand, the paper explains how the water isotopes are used in the study of the Antarctic Ice Sheet as climatic archives as well as how they allow to understand the formation of more than 200 m of lake ice present above the liquid water of subglacial Lake Vostok in East Antarctica. This case study approach demonstrates that stable water isotopes can be an ideal tool to account for many processes active in the physical environment.